Pendampingan dan Pemberdayaan Wanita Dalam Mengembangkan Digital Marketing Produk Kuliner Berbasis Mangrove Di Desa Pantai Mekar - Satria, Budi; Untari, Dhian Tyas; Putri, Amelia; Anjani, Allisya Andrea; Natalia, Friska; Cantika, Marisa (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
Based on the results of initial observations conducted by the team in the PKK community in Pantai Mekar Village, there are at least 3 aspects of problems related to women's empowerment, namely: the majority of families in Pantai Mekar Village depend only on their husband's income, so it can be said that women in Pantai Mekar Village are less empowered Economically, Pantai Mekar Village is an area in Bekasi which has a fairly extensive mangrove forest. At present, mangrove products such as dodol mangrove, mangrove syrup and crispy crab have been created. It's just that currently the packaging is still very simple, so it can't compete with similar products on the market. Products that are very innovative at this time do not have a massive marketing system. The current marketing pattern is still very simple, it only includes bazaars which are sometimes held by the local government. On the other hand, a more modern marketing system is needed for the introduction and market penetration process. PKK Desa Pantai Mekar has tried to make culinary delights made from mangroves to be processed into syrup, dodol and jam. Currently, the Ubhara Jaya PKM Team and the Pantai Mekar Village PKK are also carrying out improvements in the production, marketing and licensing processes related to brands. It is hoped that Mangrove-based culinary can be a source of economic improvement for women in Pantai Mekar Village.